Effects of Commercial Sex Work on Marital Breakdown in Wukari Metropolis, Taraba State: Counselling Implications and Interventions - Fadahunsi, John A.; Adiele, Sunday; Stephen, Mathew (International Journal of Humanities, Education, and Social Sciences, 2025)
This study examined the effects of commercial sex work on marital breakdown in Wukari Metropolis, Taraba State: counselling implications and interventions. The objective of the study was to the ascertain the prevalence of commercial sex workers, identify factors that contribute to the prevalence of commercial sex workers and determine the effect of commercial sex workers (CWS) on marital breakdown in Wukari Metropolis, Taraba State and its implications for counselling. The research design adopted for the study was descriptive survey research design 400 respondents was selected through the use of multistage sampling technique. Data for the study was collected through the use of structured questionnaire and oral interview. Respondents responses was analyzed through the use of mean while Chi-square inferential statistics was used to test hypotheses for the study. Additionally, interview replies were analyzed using content analysis. Findings from the study revealed that there is prevalence of commercial sex work activities in Wukari Metropolis. Further findings from the study revealed that poverty is the most significant factor contributing to the prevalence of commercial sex workers. The study recommends that counselling programs should integrate marital counseling and should be made more accessible to individuals and couples affected by commercial sex work.